1997
DOI: 10.1128/mcb.17.7.3955
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the HS2 Enhancer toward a cis-Linked Gene Is Independent of the Orientation, Position, and Distance of the Enhancer Relative to the Gene

Abstract: The locus control region (LCR) of the human ␤-globin gene domain is defined by four erythroid-cell-specific DNase I-hypersensitive (HS) sites, HS1, -2, -3, and -4, located 50 to 70 kb upstream of the ␤-globin gene in a transcriptional direction: 5Ј HS4-HS3-HS2-HS1-//-ε-G ␥-A ␥-␦-␤ 3Ј (17,20,37,50). The LCR has been shown by studies of natural deletions of ␥␦␤-thalassemia (8,11,24) and by gene transfer experiments (14,18,20,51) to be indispensable for erythroid-cell-specific and high-level transcription of cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 55 publications
3
71
0
2
Order By: Relevance
“…1997; Kong et al 1997;Carninci et al 2005;Manak et al 2006). Overall, our results demonstrate the successful isolation of mutants with strong long-distance activation phenotypes.…”
Section: Long-distance Transcriptional Activation 603mentioning
confidence: 52%
See 1 more Smart Citation
“…1997; Kong et al 1997;Carninci et al 2005;Manak et al 2006). Overall, our results demonstrate the successful isolation of mutants with strong long-distance activation phenotypes.…”
Section: Long-distance Transcriptional Activation 603mentioning
confidence: 52%
“…Previous 59-RACE experiments showed that the HIS3 long transcript initiates proximal to the UAS (Dobi and Winston 2007). Although the level of this long transcript is variable and we do not understand its regulation, we note that transcripts initiating near enhancers have been observed in metazoans (Ashe et al 1997;Kong et al 1997;Carninci et al 2005;Manak et al 2006). Overall, our results demonstrate the successful isolation of mutants with strong long-distance activation phenotypes.…”
Section: Selection Of Polygenic Mutants That Allow Increased Transcrimentioning
confidence: 64%
“…The ␤-globin locus in humans also is divided into distinct subdomains, and long, intergenic transcripts are responsible for delineating the active domains by association with chromatin-remodeling activities (38). An active enhancer at the H2 hypersensitive site of the ␤-globin locus control region also was found to be transcribed from transgenes in mice, irrespective of the position and orientation of the enhancer (39). At imprinted loci in mice, a number of cisregulatory elements, including enhancers and the imprinting control regions at H19͞Igf2 and Igf2r, are transcribed (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…HS2 acts as a classical enhancer in transient transfection assays and in transgenic mice (6)(7)(8)(9) and has binding sites for several transcription factors (10). A tandem pair of activator protein 1 (AP1)͞NF-E2 sites possesses the core enhancing activity of HS2 (11,12).…”
mentioning
confidence: 99%